TANGGUNGJAWAB KELUARGA, PEMERINTAH DAN MASYARAKAT ATAS PENDIDIKAN - Asichul In'am (JIEM: Journal of Islamic Education and Manajemen, 2021)
The family is the first and foremost institution in the development of the individual. The formation of a child's personality starts from the family environment. One of the responsibilities of parents to children in the family is to educate their children. In essence, the obligation to educate the parents is not only because educating children is part of fulfilling psychic needs as well as members of society. The government is responsible for the development of education in Indonesia as stipulated by the Law on Teachers and Lecturers. The government also requires 9 years of study or reasonable with habituation from the School Operational Assistance Fund (DANA BOS). In the context of education, society is a group of many people with a variety of qualities ranging from the uneducated to the highly educated. Good relations with society are necessary because no one lives without the help of society